The bullwhip effect in the AR(1) demand structure - Michna, Zbigniew (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2014)
In this note we derive the famous formula of F. Chen, Z. Drezner, J.K. Ryan and D. Simchi-Levi [2000a] for the bullwhip effect measure in a simple two-stage supply chain under the assumption that demands constitute autoregressive structure of order 1. Our approach is a little different than in Chen et. al [2000a] and therefore we obtain the formula as an equality unlike Chen et. al [2000a], where they have it as a lower bound. Moreover, we analyze the bullwhip effect measure formula and in some cases we have different conclusions than in Chen et. al [2000a].
Mathematical Economics, 2014, Nr 10 (17), s. 53-60
Keywords: supply chain; Bullwhip Effect; order-up-to level policy; demand forecasting; AR(1) structure